Reconstruction of the Meaning of Riba Within the Framework of Maqasid Al-Shari'ah: A Critical Study of Al-Maraghi's and Ibn Ashur's Interpretations - Muzayyanah, Muzayyanah; Ali, A.M Hasan; Al-Fahim, Omar (STAI Publisistik Thawalib Jakarta, 2026)
The interpretation of riba in modern Islamic thought remains controversial, and the perspectives of al-Maraghi and Ibn Ashur have not been systematically compared through the lens of Maqasid al-Shari’ah. This study aims to reconstruct the meaning of riba through a comparative analysis of Tafsir al-Maraghi and al-Tahrir wa al-Tanwir using a maqasidi and critical hermeneutic approach. Employing qualitative library research, it integrates tafsir muqaran, maqasidi analysis, and critical hermeneutics to examine primary and relevant secondary literature. Findings show both scholars affirm the absolute prohibition of riba on ethical and jurisprudential grounds, yet differ methodologically: al-Maraghi emphasizes the socio-economic harm of riba, focusing on zulm and exceptions under darurah, whereas Ibn Ashur applies a maqasidi-ijtihadi framework, evaluating transactions through fitrah, maslahah, and musawah. Synthesizing their insights yields a holistic framework that emphasizes anti-exploitation (man’ al-istighfall), wealth justice (‘adalah al-tharwah), and purposive compliance (iltizam al-maqasid), which is relevant for assessing modern financial instruments in light of Shari’ah objectives. Reconstructing Riba based on maqasid offers a contemporary, just, and anti-exploitative framework for Islamic economic jurisprudence, extending Islamic hermeneutics and providing practical guidance for modern financial regulation and practice.